A Critical Analysis of the Use of the Verb ἀναγινώσκω in the Corpus Paulinum: A Reappraisal of the Reading Practice in Early Christianity - De Feo, Stefano (Annali di scienze religiose, 2020)
This article focuses on the value of reading in early Christian communities, starting from a critical analysis of the use of the lexical field of ἀναγινώσκω in the Pauline correspondence. Along with this analytical method, this contribution deals with the most important features of the reading practice in antiquity; subsequently, it analyses in detail the occurrences of the verb ἀναγινώσκω in the Corpus Paulinum, drawing particular attention to the incompatibility of the public reading of these Letters and the liturgical reading of the Scriptures. In fact, if one considers the proto-Christian literary phenomenon, it is noteworthy that right from his first Letter (I Thess 5. 27), Paul exhorts his audience to undertake a public reading of it. Indeed, it is Paul’s wish that his Letter reach the whole Thessalonian community through a communal reading. This difference can be documented through the divergent description of these approaches to the text given by Paul himself, attesting both the practice of public reading in the early Christian communities (II Cor 1. 13) and the liturgical memory of the First Testament (II Cor 3. 14-15). This research purposes to show the development and the progressive acquisition of significance of the reading practice in the Pauline communities: the liturgical reading of Paul’s Letters is regarded as the crowning of their interpretation and not as the starting point of their reception. In the light of the canonization process of Paul’s Letters, Eph 3. 4 constitutes, more than Col. 4. 16, an increase in value of the reading practice and, at the same time, it bears witness to the progressive acquisition of the Corpus Paulinum as Holy Scripture. The centrality of the reader for the community arises from I Tim 4. 13, which shows that literacy might be considered as ratio seminalis in the management of the first hierarchical architecture in the Pauline Churches.